PENGAWASAN DINAS PERHUBUNGAN DALAM MENGATASI LALU LINTAS DI KOTA PEKANBARU TAHUN 2023 - Putri, Rismaya Leginta; ', Ishak (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Congestion is a traffic problem that remains unresolved. Congestion is caused by heavy traffic, increasing vehicle volumes, and public disregard for traffic regulations. Pekanbaru City is one of the cities with high levels of congestion, necessitating traffic supervision to ensure safe, secure, fast, smooth, orderly, and secure traffic flow. The theory used in this study is Griffin's supervision theory, which has four stages of supervision. The research method used in this study is a descriptive qualitative approach, with data sources through interviews with members of the Pekanbaru City Transportation Agency. The results of this study are: 1) The traffic supervision standards that serve as a reference in all aspects of the Pekanbaru City Transportation Agency's performance are based on Law No. 22 of 2009. 2) The performance of Pekanbaru City Transportation Agency employees will be measured through written and verbal reports, which can include photo documentation in the field. 3) Comparing employee performance results with existing standards, an evaluation meeting will be held regarding employee discipline in carrying out supervisory duties through the reports received. 4) The corrective actions taken by the Pekanbaru City Transportation Agency against its employees include issuing warning letters to several employees who lack discipline and conducting raids on third-party traffic controllers (Pak Ogah). Factors hindering the traffic monitoring process include external factors originating from third-party traffic controllers (Pak Ogah) and internal factors originating from the Transportation Agency's own human resources. Traffic monitoring conducted by the Transportation Agency has been quite effective, but several obstacles have been encountered during its implementation. Keywords: Supervision, Congestion, Traffic.